2002
DOI: 10.1179/mnt.2002.111.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of progressive fracture and associated behaviour of mine pillars by use of a local degradation model

Abstract: Fracture of mine pillars is a progressive process that comprises, within the material of the pillar itself, the creation of cracks, alteration of the local material properties, disturbance of local stress fields, extension of local failures and the formation of fracture planes. The physical occurrence of these processes leads to nonlinear, macroscopic mechanical behaviour of fracturing pillars and an associated loss of load-carrying capability.A local degradation model recently developed by the authors has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…In this approach, Weibull distribution function was used to present the elemental heterogeneity similar to RFPA and innovatively a degradation index was introduced to incorporate the confinement effects. The approach was successfully applied to failure process of rock specimens in laboratory experiment [ 63 ] and some rock projects in engineering scale [ 64 ]. The results showed that the confinement effect can be well reflected in this approach, e.g., stress-strain relations that evolve from brittle to ductile as well as fracture patterns that evolve from axial splitting to shear to dilatancy as confinement increases [ 63 ].…”
Section: The Numerical Approachmentioning
confidence: 99%
“…In this approach, Weibull distribution function was used to present the elemental heterogeneity similar to RFPA and innovatively a degradation index was introduced to incorporate the confinement effects. The approach was successfully applied to failure process of rock specimens in laboratory experiment [ 63 ] and some rock projects in engineering scale [ 64 ]. The results showed that the confinement effect can be well reflected in this approach, e.g., stress-strain relations that evolve from brittle to ductile as well as fracture patterns that evolve from axial splitting to shear to dilatancy as confinement increases [ 63 ].…”
Section: The Numerical Approachmentioning
confidence: 99%
“…This model has successfully been implemented to simulate the fracturing process of rock in mine pillars [64], laboratory scale rock specimens in compression [65], and excavation of a circular opening [66]. In all cases the model produces convincing fracture patterns and realistic complete stress-strain curves corresponding to different stress states.…”
Section: Article In Pressmentioning
confidence: 99%
“…Progressive mechanical breakdown of rock can be simulated using statistical modelling in conjunction with CDM when implemented within such commonly used continuum based numerical methods as FEM and FDM [60][61][62][63][64][65][66]. One such example is that developed by Tang et al [60], whereby the microstructural heterogeneity of the rock material is represented by values of elemental strength and elastic modulus, both of which are described by the Weibull distribution function [59].…”
Section: Cdm Based Statistical Modelsmentioning
confidence: 99%
“…This model uses an elemental constitutive relation to describe degradation in both the strength and stiffness of rock, with the result that failure occurs randomly and progressively within a volume of rock. The model has successfully been implemented to simulate the fracturing process in both mine pillars [17] and laboratory scale rock specimens in compression [18]. In both cases the model produces convincing fracture patterns and realistic complete stress-strain curves corresponding to different stress states.…”
Section: Introductionmentioning
confidence: 99%